Traditional Malay midwifery practices for body treatment (Param) and forehead treatment (Pilis) in Kelantan, Terengganu, Pahang and Johor of Malaysia - Othman, Rashidi; Ramya, Razanah; Ishak, Nooriszai (2014)
Midwifery is the practice of assisting a woman through childbirth using natural procedures with limited access to biomedicine. However, today in Malay community, midwifery continues to play an important role in both traditional and modern cultural settings that involved with providing health care during pregnancy, childbirth and postnatal care to both mother and newborn. Param or outer body treatment and Pilis known as forehead treatment are two famous traditional Malay midwifery practices among Malay culture and exhibit a wide variation in plant materials selection. This study established that plant materials selection differs with Malay midwifery practices, locality, environmental factors and culture. A total of 19 Malay midwives were observed in four different states of Malaysia in Kelantan, Terengganu, Pahang and Johor. There were at least 8 most common plant materials used at all 4 localities during Berparam which are lime, Lengkuas, Kunyit, Cekur, Halia, Halia bara, garlic and Serai wangi. Surprisingly none were similar in plant composition selection during Berpilisat all localities. At Kelantan and Terengganu 2 species were used whereas in Pahang 3 species and Johor 9 species were used during Berpilis. All plant materials composition for Berpilis at 4 different states was not similar. Paradoxically, for Berparam, many similarities in term of species used from Kelantan, Pahang and Terengganu whereas from Johor the selection of plant materials were also quite similar. The study highlighted on traditional Malay midwifery practices (Param and Pilis) in creating ethnic’s identity and sense of place for landscape ethno-botany planting design in particular locality.